Long-term follow-up of patients surgically treated for ruptured ovarian endometriotic cysts - Yu-Hsin Huang; Jui-Der Liou; Chia-Lin Hsieh; Chii-Shinn Shiau; Liang-Ming Lo; Ming-Yang Chang (Elsevier, 2011)
Objective: Approximately 4% of women are admitted to hospitals because of ovarian cyst rupture, hemorrhage, or torsion. Endometriotic cyst rupture is a rare surgical emergency associated with severe peritonitis and pelvic adhesion, and we aimed to determine its prognosis and long-term outcome. Materials and Methods: We reviewed and analyzed the medical records of 11 patients (mean age, 31.8±7.2 years) with ruptured endometrioma and a history of dysmenorrhea (4.9±2.3 of maximum 10) who were surgically treated, and then regularly followed-up for more than 3 years (range, 35-261 months). Results: Previous ultrasound examinations revealed pelvic cysts in seven patients. Three patients had a history of endometrioma surgery. In the emergency room, eight patients complained of uterine motion tenderness. Sonography revealed residual ovarian tumors (size range, 4.2-10.4 cm), with or without fluid accumulation in the cul-de-sac. Surgical enucleation by laparoscopy or laparotomy revealed high revised American Fertility Society endometriosis scores (78±20.1) as well as high adhesion scores (48.7±11.3). In the postoperative period, four patients had recurrent ovarian tumors that were related to elevated serum cancer antigen 125 levels and high postoperative pain scores. In contrast, three patients who became pregnant during the postoperative period had low serum cancer antigen 125 levels and pain scores. Conclusion: Endometrioma rupture should be considered in females presenting with sudden lower abdominal pain, associated with a history of dysmenorrhea and preexisting pelvic cysts. Emergency surgical intervention may lead to a better prognosis, particularly in patients without a history of previous endometrioma surgery.